자기공진방식의 무선전력전송 시스템에서 공진 중계기 적용 여부에 따른 전력전송 효율 분석 - 백승명(Seung-Myung Baek); 김동은(Dong-Eun Kim); 손진근(Jin-Geun Shon) (전기학회논문지 P, 2018)
In this paper, the power transfer efficiency analysis based on the resonant repeater in a magnetic resonance wireless power transfer system is proposed. The efficiency of the magnetic resonance method was verified by comparing the general frequency with the resonance frequency. The resonance repeater was arranged to increase the efficiency and increase the transfer distance. When using resonant repeaters, the maximum efficiency increase is about 36.23[%] and the transfer distance was extended to more than 20[cm]. Through this study, confirmed the effect of using resonance repeaters in wireless power transfer system. As a result, it can be expected that the overall technology related to wireless power transfer system will be more valuable for energy-IT technology.